Perspektif Islam dalam Pendidikan Agama Islam dan Pekerjaan Sosial: Implikasi terhadap Pengajaran dan Praktik - Arifin, Zaenal; Tafsir, Ahmad; Ahmad, Asep (ANWARUL, 2023)
Many countries in the world have incorporated social work into their education systems. This is since many cultures have found creative ways to help improve their communities through traditional means. In addition, many have taken advantage of practices from their native cultures to add new perspectives to social work. Currently, there is a shortage of academic material on Islamic social work. The authors predict that this will be corrected soon due to increased academic interest. In this era, a personal perspective is presented on the dilemmas and ambiguities posed by Islamic religious education and social work in Indonesia.